A competência das CPCJ no apadrinhamento civil e comparação com a regulação do exercício das responsabilidades parentais a favor de terceiro e com a adoção restrita - Dias, Catarina Miranda Soares da Costa (2017)
The purpose of this Internship Report was to study the role of the Children’s Protection Commission in the civil godfathering and compare this institute with the parental responsibilities and the already revoked restrict adoption, to understand if there are advantages on creating this legal bind in comparison to the others and in which way. Were determined as advantages: the less demanding requirements; the easier way to dismiss the consent for the creation of this bind than it was for the restrict adoption and the easier way to revoke it, the fact that there aren’t any succession rights or last name changes; the benefits in terms of taxes, work absences and licenses for care and social benefits for the godparents. But the civil godfathering is not a stranger to criticism from the legal doctrine, being some of the censure: the discrimination of the godchildren in relation to the godparent’s children; the constant interaction that is required between the godparents and the godchild’s biological family which may lead to conflict and the contact permission that is given to the ex-godparents after the godfathering being revoked. Other problems exist, such as: the time that passes between the approval from the court of the godfathering compromise signed in the Children’s Protection Commissions and the extension of it when the compromise needs to return to them to be corrected and to be submitted to the court once again; the need to insert clauses minding alimony, visitation rights and limitations to the parental responsibilities, when the Commissions have no powers to decide and change them and also the lack of knowledge of the institute coming from it being in a different legal diploma, from the amount of cases that exist in each Commission and from the lack of legal technicians in these entities.